IMPLEMENTASI RENCANA PENGELOLAAN SEKTOR PERIKANAN (STUDI DIREKTORAT NASIONAL PERIKANAN DAN BUDIDAYA / DNPA KEMENTRIAN PERTANIAN DAN PERIKANAN MAP Dili Timor-Lestế) - Maria De A. Dias X (Universitas Tribhuwana Tunggadewi, 2015)
The implementation at DNPA domain is organized by the stakeholders of the ministry. Decision is made based on consultation with stakeholders in the domain of ministry or ministerial line at ministry and junior minister offices. Some actors play important role in the implementation of planning and management policy for fishery sector. The actors may not only include governmental institutions but also private and community. Communication is a very important matter within institution and organization. Resources represent an important factor in the implementation of an activity or task because without resource, the assignment is hardly executed. Bureaucracy is a structure comprising of routine operational assignments that must be accomplished through specialization, regulation and quite formal stipulation.